EDUTAINMENT STRATEGY OF @ROLANSIHOMBING TIKTOK ACCOUNT: BUILDING AUDIENCE ENGAGEMENT THROUGH EDUCATIONAL AND ENTERTAINING CONTENT - Tuty Alawiyah Pulungan; Al-Hafizh Mubarak Hamdan (Academic Solution Publisher, 2025)
This study analyzes the edutainment strategy used by the TikTok account @rolansihombing_ to build audience engagement through educational running-themed content. The study employed a qualitative approach with content analysis, supported by data collection techniques such as non-participant observation and literature review. The results indicate that the most consistently used primary strategy is personal storytelling combined with humor, demonstrative visualizations, and a delivery style tailored to the characteristics of the TikTok platform. This combination makes technical information such as the concept of